Measurements of activity coefficients at infinite dilution of organic solutes and water on polar imidazolium-based ionic liquids - Martins, Mónia A.R. (2016)
The activity coefficients at infinite dilution, gamma(infinity)(13), of 55 organic solutes and water in three ionic liquids with the common cation 1-butyl-3-methylimidazolium and the polar anions Cl--,Cl- [CH3SO3](-) and [(CH3)(2)PO4](-), were determined by (gas + liquid) chromatography at four temperatures in the range (358.15 to 388.15) K for alcohols and water, and T = (398.15 to 428.15) K for the other organic solutes including alkanes, cycloalkanes, alkenes, cycloalkenes, alkynes, ketones, ethers, cyclic ethers, aromatic hydrocarbons, esters, butyraldehyde, acetonitrile, pyridine, 1-nitropropane and thiophene. From the experimental gamma(infinity)(13) values, the partial molar excess Gibbs free energy, (G) over bar (E infinity)(m), enthalpy (H) over bar (E infinity)(m), and entropy (S) over bar (E infinity)(m), at infinite dilution, were estimated in order to provide more information about the interactions between the solutes and the ILs. Moreover, densities were measured and (gas + liquid) partition coefficients (KL) calculated. Selectivities at infinite dilution for some separation problems such as octane/benzene, cyclohexane/benzene and cyclohexane/thiophene were calculated using the measured gamma(infinity)(13), and compared with literature values for N-methyl-2-pyrrolidinone (NMP), sulfolane, and other ionic liquids with a common cation or anion of the ILs here studied. From the obtained infinite dilution selectivities and capacities, it can be concluded that the ILs studied may replace conventional entrainers applied for the separation processes of aliphatic/aromatic hydrocarbons.